(untitled) - Peters-Golden, Holly (Boston, 2002)
This volume is an introduction to fifteen societies, and each glimpse is brief and necessarily in complete. It is my hope that any student who is intrigued will look further into the past and present lives of these people. As such, the chapters are aimed more at sparking interest than appeasing it.
Keywords: Ethnology